Audit Committee Effectiveness and Environmental, Social and Governance Rating in Malaysia - Jamil, Nurul Nazlia; Wahyuni, Ersa Tri (International Journal of Economics and Financial Issues, 2024)
The purpose of this research is to ascertain the impact of audit committee effectiveness and the environmental, social and governance (ESG) rating for public listed firms in Malaysia. This paper aims to understand how AC effectiveness (ACEF) such as size, independence, meeting and expertise influence the ESG rating. Given that ESG rating is part of corporate reporting, the reporting practice of ESG should therefore be part of the AC’s effectiveness. The study uses a sample of 237 listed companies for the year 2023 that discloses ESG rating based on the FTSE Russel rating model. The rating model consists of 3 individual pillars and 14 themes. The collected data was then analyzed through regression analyses. The disclosure of ESG rating was regressed against the AC effectiveness, controlling for firm size, return on asset (ROA) and leverage. The results show a significant positive effect of AC effectiveness on ESG rating for the firms in Malaysia. Individually, AC independence, firm size, ROA and leverage also indicate a positive and significant relationship with the ESG rating. The paper validates the significant of the AC control mechanism in improving the ESG rating hence offering a potential answer to reduce agency and legitimacy issues of firms in Malaysia. This study deepened the understanding about the functions of AC beyond the traditional and compulsory roles to oversee the financial reporting process. Empirical evidence that AC effectiveness leads to a better corporate disclosure practice had also been presented.